2009
DOI: 10.1111/j.1469-8749.2009.03310.x
|View full text |Cite
|
Sign up to set email alerts
|

The co‐occurrence of autism and birth defects: prevalence and risk in a population‐based cohort

Abstract: Aim  To estimate the prevalence of major birth defects among children with autism, the prevalence of autism in children with birth defects, and the risk for autism associated with having birth defects. Method  Retrospective cohort including all children born in Atlanta, GA, USA, 1986 to 1993, who survived to age 3 years and were identified through Georgia vital records. Children with autism and other developmental disabilities residing in Atlanta at ages 3 to 10 years in 1996 were identified through the Metrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 33 publications
3
30
0
Order By: Relevance
“…There is strong evidence that fetal valproate exposure is associated with elevated rates of birth defects, 37 and that birth defects and autism often co-occur. 17 Our data suggest that there is an elevated risk of ASD independent of the presence of major birth defects, and highlight the importance of continued monitoring of exposed children beyond infancy, particularly in those for whom initial surveillance is unremarkable.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…There is strong evidence that fetal valproate exposure is associated with elevated rates of birth defects, 37 and that birth defects and autism often co-occur. 17 Our data suggest that there is an elevated risk of ASD independent of the presence of major birth defects, and highlight the importance of continued monitoring of exposed children beyond infancy, particularly in those for whom initial surveillance is unremarkable.…”
Section: Discussionmentioning
confidence: 56%
“…16 Children with major birth defects or a diagnosis of epilepsy were excluded, as these conditions are known risk factors for ASD. 17,18 Between November 2007 and May 2010, 175 women with 190 children aged 6-8 years were identified from the APR and invited to participate in the study. Mothers of 27 children (14%) declined to participate.…”
Section: Participantsmentioning
confidence: 99%
“…It is likely that these rates are under-reported because investigation of ASD co-occurring conditions was not the focus of the ADDM surveillance effort. However, a cohort study of children in Georgia found a similar prevalence of chromosomal disorders and Down syndrome in persons with ASD (Schendel et al, 2009). …”
Section: Resultsmentioning
confidence: 98%
“…Among children who met a surveillance definition for an ASD, 55 % had abnormal mood or affect compared to 26 % of children with at least one symptom of an ASD but no ASD diagnosis (Schendel et al, 2009). The Special Needs Autism Project in the UK found 44 cases of emotional disorder per 100 children with ASD (Simonoff et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Whether these conditions arise independently of ASDs as a consequence of the core ASD deficits or as an endophenotype that predisposes a child to have an ASD or can be attributed to the underlying neuropathologic abnormalities is not clear. Individuals with an ASD are more likely than the general population to have major congenital anomalies, especially those individuals with a co-occurring intellectual or other disability (Hultman et al 2002; Schendel et al 2009; Wier et al 2006). Children with autism who have dysmorphic features also are more likely to have a known genetic syndrome or a structurally abnormal brain, compared with children with autism who do not have dysmorphic features (Miles and Hillman 2000).…”
Section: Seed Scientific Background and Aimsmentioning
confidence: 99%